FAKTOR–FAKTOR YANG MEMPENGARUHI PENANAMAN MODAL ASING DI ASEAN PERIODE 2000-2013 - Olivia Tanaya; Suyanto Suyanto; Firman R Djoemadi (Jurnal Ekonomi dan Bisnis, 2015)
This study is a replication of the results of research Alam and Shah (2013). This study aims to identify and analyze the factors that influence the foreign direct investment (FDI) in ASEAN in 2000-2013. GDP growth in every country is important to be maintained in order not to decrease due to the growth of GDP will reflect the country's economic growth. Foreign direct investment (FDI) is one way to increase GDP growth. AEC 2015 will facilitate the access of FDI in ASEAN countries so that the opportunity to develop a PMA needs to be optimized. Factors tested in this study, namely market size, labor force, labor productivity, the corporate tax rate, trade openness, political stability, exchange rate, inflation, and the quality of infrastructure. Data management is using Ordinary Least Square is a method of data panel with software E-views 6. The data used are secondary data obtained from the World Bank, The Conference Board, and KPMG. These results indicate that the market size and political stability is a variable that can attract FDI into the country. The higher the value of market size and its political stability, the value of FDI entry also higher.